2012
DOI: 10.1097/mpa.0b013e31823bcef2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of FOXM1 Is Associated With Poor Prognosis and Clinicopathologic Stage of Pancreatic Ductal Adenocarcinoma

Abstract: Our finding indicates that FoxM1 could be used as prognostic molecular marker and therapeutic target for PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…Dual luciferase assays revealed that STAT3 is directly targeted by miR130b, which was further confirmed by the inverse expression of miR-130b and STAT3 in pancreatic cancer specimens [66]. Recently, another transcription factor named FOXM1 is perceived to play an important role in pancreatic cancer progression [67]. Notably, FOXM1 overexpression is responsible for acquisition of the EMT and CSC phenotypes, which is mediated in part by the regulation of miR-200b expression [68].…”
Section: • Crosstalk Between Mirnas and Transcription Factors In Pancrementioning
confidence: 87%
“…Dual luciferase assays revealed that STAT3 is directly targeted by miR130b, which was further confirmed by the inverse expression of miR-130b and STAT3 in pancreatic cancer specimens [66]. Recently, another transcription factor named FOXM1 is perceived to play an important role in pancreatic cancer progression [67]. Notably, FOXM1 overexpression is responsible for acquisition of the EMT and CSC phenotypes, which is mediated in part by the regulation of miR-200b expression [68].…”
Section: • Crosstalk Between Mirnas and Transcription Factors In Pancrementioning
confidence: 87%
“…Some studies also showed the same results. Xia et al found that a high level of expression of FoxM1 was significantly correlated with clinical staging (P = 0.00), lymph node metastasis (P = 0.01), and histological differentiation (P = 0.02) in pancreatic ductal adenocarcinoma (Xia et al, 2012). Chu et al revealed that high FoxM1 expression was closely correlated with the presence of lymph node metastasis, incidence of liver metastasis, and advanced TNM stage in colorectal cancer (Chu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The staining score was categorized into two groups as weak/negative staining (score < 4) and strong staining (score ≥ 4) (Liu et al, 2011;Xia et al, 2012). The highest labeling score among the three tissue sections was entered for statistical analyses.…”
Section: Immunohistochemical Staining For Foxm1mentioning
confidence: 99%
“…Elevated expression of FOXM1 has been detected in a wide range of human tumors and has been implicated in cellular transformation, tumor initiation and progression (7). Accumulating evidence demonstrates that increased expression of FOXM1 is associated with poor prognosis in various types of cancers (8)(9)(10)(11), including MB (12). Furthermore, previous studies have shown that FOXM1 mediates resistance to a diverse spectrum of anticancer drugs in breast cancer (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%